Analysis of QRIS Usage, Digital Marketing, and Entrepreneurial Leadership on MSME Revenue in Denpasar - Utami, Eva Yuniarti; Uli, Nur Zarliani (Eastasouth Institute, 2025)
This study investigates the impact of QRIS adoption, digital marketing, and entrepreneurial leadership on the income of MSMEs in Denpasar. Employing a quantitative research design, data were collected from 200 MSMEs using a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal significant positive relationships between QRIS adoption (β = 0.35), digital marketing (β = 0.42), and entrepreneurial leadership (β = 0.28) with MSME income, collectively explaining 64% of the variance in income. These findings underscore the importance of digital tools and proactive leadership in enhancing MSME performance. The study provides theoretical insights and practical recommendations to accelerate digital transformation and leadership development in MSMEs.